Incremental semantic scales by strings, - FERNANDO, RAFAEL TIMOTHY (Association for Computational Linguistics, 2014)
Scales for natural language semantics are analyzed as moving targets, perpetually under construction and subject to ad- justment. Projections, factorizations and constraints are described on strings of bounded but refinable granularities, shap- ing types by the processes that put seman- tics in flux.
Proceedings of the EACL 2014 Workshop on Type Theory and Natural Language Semantics
Type Theory and Natural Language Semantics
Keywords: natural language semantics